GENDER-BASED PERFORMANCE DIFFERENCES IN INSTITUTIONAL TOEFL-PREDICTION TEST: A PBT-STYLE PRE-TEST AND POST-TEST STUDY - Ayubadiah, Fitrahnanda; Ningsih, Era Wahyu (Faculty of Letters Universitas Balikpapan, 2025)
This study investigates gender-based performance differences in the Institutional Test of English as a Foreign Language (TOEFL) modeled on the Paper-Based Test (PBT) like format. A total of 261 Indonesian undergraduates (56 males, 201 females) completed a pre-test, participated in a one-month TOEFL preparation program, and then sat for a post-test. Using a mixed-method design, the study analyzed section-specific score gains and interpreted the results through classroom observations of participation and engagement. The findings revealed that female students showed greater gains in Listening and Structure, whereas male students showed stronger improvement in Reading and obtained higher overall score gains. Moreover, female learners were more visibly engaged during instruction, frequently asking questions and taking notes, while male learners tended to participate less in class but appeared to rely on independent strategies, particularly for reading tasks. These findings highlight that gendered participation styles may shape section-specific outcomes in PBT-style testing. The study underscores the importance of gender-responsive instructional strategies in TOEFL preparation programs and calls for greater attention to fairness in the design and use of locally developed prediction tests.